2007
DOI: 10.1186/1471-2458-7-344
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of new pulmonary tuberculosis in Guangzhou, China 1993–2002: a register-based cohort study

Abstract: BackgroundCompletion of treatment for tuberculosis (TB) is of utmost priority for TB control programs. The aims of this study were to evaluate the treatment outcome of TB cases registered in Guangzhou during the period 1993–2002, and to identify factors associated with treatment success.MethodsTwo (of eight) districts in Guangzhou were selected randomly as objects of study and their surveillance database was analyzed to assess the treatment outcome and identify factors associated with treatment success for TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
23
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 14 publications
10
23
2
1
Order By: Relevance
“…The treatment success rate of TB in this study was 64.6%, which is less than the 2017 WHO report, where the treatment success rate among 30 high TB burden countries varied from 71% to 94% [1] and the national report of overall treatment success rate in Ethiopia (83.7%) [19]. Moreover, the treatment success rate in the current study is still below the treatment success rate reported in Bahir Dar, Ethiopia, 80.8% [18], Tigray, Ethiopia, 89.2% [20] and China, 88% [12]. The low treatment success rate observed in this study might be due to a high death rate (16.5%) and transferred out rate (10.4%).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The treatment success rate of TB in this study was 64.6%, which is less than the 2017 WHO report, where the treatment success rate among 30 high TB burden countries varied from 71% to 94% [1] and the national report of overall treatment success rate in Ethiopia (83.7%) [19]. Moreover, the treatment success rate in the current study is still below the treatment success rate reported in Bahir Dar, Ethiopia, 80.8% [18], Tigray, Ethiopia, 89.2% [20] and China, 88% [12]. The low treatment success rate observed in this study might be due to a high death rate (16.5%) and transferred out rate (10.4%).…”
Section: Discussioncontrasting
confidence: 74%
“…A study conducted in Gondar, Ethiopia showed that the treatment success rate of tuberculosis patients was unsatisfactorily low and it became a serious public health concern [11]. Being male, older age [12][13][14], smear-negative pulmonary or extrapulmonary tuberculosis and being rural resident was associated with lower treatment success rate [4,11]. Therefore, TB control programs should be strengthened to prevent unnecessary deaths [14].…”
Section: Introductionmentioning
confidence: 99%
“…El anterior hallazgo fortalece la idea de que la meta de curación de 85%, propuesta por la OMS, es posible en el contexto de la estrategia "Alto a la TB". Esto se ha evidenciado en otras cohortes que han registrado el aumento en las tasas de éxito terapéutico desde la implementación de la estrategia DOTS (24,25).…”
Section: Discussionunclassified
“…In Table 1, CSOZ means Central Statistics Office of Zimbabwe, a* denotes parameter values and ranges from Dye et al (1999), Dye and William (2000), b* denotes parameter values from , c* denotes parameter values from Qing-Song Bao et al (2007) and d* denotes parameter values from Bhunu et al (2008). Due to lack of data, the remaining parameters are assumed within realistic ranges (for the purpose of illustration) based on current understanding of the qualitative and synergistic relationships between smoking and TB and their essential biological and epidemiological features.…”
Section: Numerical Simulationsmentioning
confidence: 99%